MODIFICATION OF H-ZSM5 CATALYST WITH ZINC METAL FOR BIOGASOLINE PRODUCTION FROM PALM OIL - Yumna, Saffanah
During the period of 2015—2022, Indonesia has imported 26M kL of refined oil products with gasoline contributing 78%. Palm oil has the potential to be an alternative fuel source due to its structure similarity to gasoline, relatively easy to be cracked and aromatized, and Indonesia’s status as largest palm oil producer. Previous research showed that catalytic cracking with the aid of H-ZSM5 catalyst is one of the optimal methods for converting palm oil into biogasoline. High amount of gas content (olefin and light paraffin) in the product became problematic with this method. Active zinc (Zn) as a promoter can enhance the aromatization process, achieving a better liquid fraction yield (Chen et. al, 2015). The characteristics of the Zn-HZSM-5 catalyst were analyzed using XRD, XRF, NH3-TPD, and BET methods. The gasoline were tested using GC-DHA and GC-SIMDIS. Gaseous products were analyzed with GC-Perkin Elmer and GC-FID. Produced cokes were calculated by TGA Gravimetry method. This study utilized cooking oil (RBDPO) as the feedstock. The H-ZSM5 catalyst were made from the Na-ZSM-5 catalyst synthesized by TRKK ITB laboratory. The catalytic cracking processes were conducted in a fixed-bed reactor at a temperature of 500 °C with a WHSV of 2.5 h-1. Incorporation of Zn metal increased the gasoline and aromatic content. Optimal gasoline was attained at 2,5% Zn loading with 47.72%-w of gasoline, aromatic content of 97.09%-w, and a 119.16 RON. The increase in gasoline is caused by the shifting of strong acid content to weak/medium acid contents by 13.6%, which can prevent overcracking and increase aromatization. Reduction of calcination steps (2,5-IMZnZSM5) reduced feed oil conversion to OLP by 9—10%-wt but has no impact on the product’s gasoline concentration and aromatic content. Spent catalysts showed a degeneration of catalyst activity. Meanwhile, regenerated catalysts showed an increase of acidity, crystallinity, and pore surface area.